2023
DOI: 10.2340/actadv.v103.5261
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dermatitis Patients’ Preference on Patient Self-administered Tools Used in Clinical Practice

Abstract: is missing (Short communication)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The assessment of disease severity by a caregiver can greatly impact treatment adherence of the patient ( 40 ). In this study, we identified a higher proportion of female caregivers among children with AD, and the odds of developing severe AD were reduced by 39% among AD children with female caregivers compared to male caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of disease severity by a caregiver can greatly impact treatment adherence of the patient ( 40 ). In this study, we identified a higher proportion of female caregivers among children with AD, and the odds of developing severe AD were reduced by 39% among AD children with female caregivers compared to male caregivers.…”
Section: Discussionmentioning
confidence: 99%